Profile Analysis of Handwashing Behavior Among a Sample of College Students in the Multi-Theory Model Framework - Miguel Antonio Fudolig; Robert E. Davis; Kavita Batra; Manoj Sharma (Hygiene)
Maintaining proper hand hygiene is crucial in preventing the spread of infections and other communicable diseases. It is imperative to determine the factors that affect the likelihood of initiating and maintaining the recommended handwashing behavior, especially during a pandemic. This quantitative, secondary study employed a latent profile analysis (LPA) to identify the different attitudes toward behavior change based on the Multi-Theory Model (MTM) framework in the context of following the guidelines provided by the Centers for Disease Control and Prevention (CDC) during the COVID-19 pandemic. Data were collected from 602 college students at a large university in the southern region of the United States (U.S.) in 2020. Seven distinct profiles were identified, each reflecting unique attitudes toward following the recommended handwashing guidelines. Age (p < 0.01) and gender (p < 0.01) disparities were observed between profiles. This study is the first to apply LPA within the MTM framework and provides new insights for the development of targeted interventions based on the construct score profile.